The application of Munby's taxonomy of language skills for the design of a communicative course in English for teacher trainees in KwaZulu - Odendaal, Maria Susanna (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Ed.) -- University of Stellenbosch, 1985.